CuO based solar cell with V2O5 BSF layer: Theoretical validation of experimental data. (March 2021) - Ahmmed, Shamim; Aktar, Asma; Tabassum, Samia; Rahman, Md. Hafijur; Rahman, Md. Ferdous; Md. Ismail, Abu Bakar
Abstract: In this article, the experimental and simulation study of a novel heterostructure (ITO/ZnO/CuO/V2 O5 /Ag) of the cupric oxide (CuO)-based solar cells have been presented. The heterojunction of the CuO-based solar cell was fabricated using an inexpensive and environmentally benign sol-gel spin coating technique. The structural properties of the fabricated solar cell were studied using an X-ray diffractometer and a scanning electron microscope. The simulation study of the designed CuO-based heterojunction solar cell was conducted by the SCAPS-1D simulator. The experimental photovoltaic parameters were theoretically validated. The performance of the solar cell was optimized through the further numerical investigations of the effect of thickness and carrier concentration of CuO absorber and vanadium pentoxide (V2 O5 ) back surface field (BSF) layer, defect density at CuO absorber and ETL/absorber interface layer and optical loss at the front surface of the solar cell. The optimized solar cell exhibited a power conversion efficiency (PCE) of 12.09% with VOC, JSC, and FF of 0.748 V, 24 mA/cm 2, and 67.4%, respectively. Graphical abstract: Image 1 Highlights: A novel heterostructure of CuO-based solar cell was designed, simulated and experimented. The experimental solar cell was validated through a theoretical model. The highest PCE of 12.09% was observed from the optimized solar cell.